Single atom catalyst based on carbon nanotube and manufacturing method thereof
Patent Information
- Application Number
- KR1020230085566
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-03-28
- Filing Date
- 2023-07-03
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-07-03
Smart Images

Figure 112023072766715-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a nano-carbon-based single-atom catalyst with high strength and high specific surface area and a method for manufacturing the same. Background Technology
[0003] Metal-supported catalysts are widely used in various industrial fields due to their high activity, selectivity, and stability, and research has been conducted to highly disperse the metal into small sizes to maximize the utilization of expensive metals.
[0004] In particular, single-atom-sized metal catalysts exhibit different catalytic activities due not only to the high dispersion of the metal but also to electrical properties distinct from those of conventional metal catalysts. Furthermore, these catalysts are attracting significant attention because they can maximize catalytic activity and demonstrate high chemoselectivity compared to catalysts with metal clusters containing multiple active sites, as their active sites are extremely limited.
[0005] However, single-atom-sized metals are highly unstable because they have a tendency to aggregate to maximize their surface energy. Therefore, single-atom-sized metal catalysts can only be synthesized by using a catalyst support that allows the metal to be stabilized even at the single-atom level through strong bonding. Most catalyst supports capable of stabilizing the metal at the single-atom level through strong bonding are insulators or ceramics. Since these insulator or ceramic supports possess excellent mechanical strength, a top-down approach has been used to introduce metal atoms by adsorbing them and then applying strong energy (e.g., a ball mill). However, insulator or ceramic supports have low electrical conductivity and are unstable under electrochemical conditions, making it nearly impossible to apply single-atom-sized metal catalysts supported on these supports to electrochemical reactions. Therefore, there is a requirement for a catalyst support that possesses high electrical conductivity while allowing the metal to be stabilized even at the single-atom level.
[0006] In order to solve the above-mentioned problem, the inventors presented a method for manufacturing a single-atom catalyst supported on a carbon support in the patent application KR10-2018-0136808, wherein a mixture of a precursor of a carbon support and a precursor of a heterogeneous element other than carbon is processed by a dry vapor phase process to support a single-atom catalyst containing a heterogeneous element other than carbon on the carbon support. However, there is still a need for a method to achieve high strength and a high specific surface area. The problem to be solved
[0008] In one embodiment of the present invention, a nano-carbon-based single-atom catalyst with high strength and high specific surface area and a method for manufacturing the same are provided. means of solving the problem
[0010] A nanocarbon-based single-atom catalyst according to one embodiment of the present invention comprises a carbon support; and a single-atom metal supported on the carbon support; wherein the carbon support may have a conical shape with an internal empty space.
[0011] The above-mentioned conical carbon support may include one or more carbon supports with one end open.
[0012] The specific surface area of the above nanocarbon-based single-atom catalyst is 550 m² 2 / g to 900m 2 / g can be a criminal.
[0013] In the XRD analysis of the above nanocarbon-based single-atom catalyst, the FWHM of the peak located at 2θ 26°±0.5 may be 1.44 or less.
[0014] The above single-atom metal may be included in a range of 0.1 wt% to 1.0 wt% based on the total weight of the nanocarbon-based single-atom catalyst.
[0015] The cross-sectional diameter of the above-mentioned open end may be 2 nm or less.
[0016] The carbon support may include one or more selected from single-walled carbon nanotubes or multi-walled carbon nanotubes.
[0017] It may be a secondary particle formed by aggregating multiple nano-carbon-based single-atom catalyst primary particles, and the average particle size (D50) of the secondary particle may be 30 nm to 160 nm.
[0018] The above single-atom metal may be supported by nitrogen elements combined with carbon elements.
[0019] A method for manufacturing a nanocarbon-based single-atom catalyst according to another embodiment of the present invention may include: a step of obtaining a first intermediate by mixing a carbon precursor and a metal precursor and processing them in a dry vapor phase process in an inert gas atmosphere; a step of obtaining a second intermediate by heat-treating the obtained first intermediate in an atmosphere that continuously supplies an oxygen-containing gas; and a step of obtaining a nanocarbon-based single-atom catalyst by heat-treating the obtained second intermediate in an atmosphere that continuously supplies ammonia gas.
[0020] In the step of obtaining a nanocarbon-based single-atom catalyst by heat-treating the second intermediate obtained above in an atmosphere where ammonia gas is continuously supplied, nitrogen gas may be mixed with the ammonia gas and supplied.
[0021] In the step of obtaining a nano-carbon-based single-atom catalyst by heat-treating the second intermediate obtained above in an atmosphere where ammonia gas is continuously supplied, the heat treatment can be performed at a temperature in the range of 550°C to 850°C.
[0022] In the step of obtaining a nano-carbon-based single-atom catalyst by heat-treating the second intermediate obtained above in an atmosphere where ammonia gas is continuously supplied, the heat treatment can be performed for 30 minutes to 180 minutes.
[0023] In the step of obtaining a second intermediate by heat-treating the first intermediate obtained above in an atmosphere in which a gas containing oxygen is continuously supplied, the heat treatment can be performed at a temperature in the range of 300°C to 400°C. Effects of the invention
[0025] A nanocarbon-based single-atom catalyst according to one embodiment of the present invention has the effect of excellent catalyst activity and selectivity by simultaneously securing high strength and high specific surface area characteristics.
[0026] A method for manufacturing a nanocarbon-based single-atom catalyst according to one embodiment of the present invention can manufacture a nanocarbon-based single-atom catalyst having high strength and high specific surface area simultaneously. Brief explanation of the drawing
[0028] FIG. 1 is a schematic diagram of a method for manufacturing a nanocarbon-based single-atom catalyst according to another embodiment of the present invention. Figure 2 shows the XRD analysis results of the catalysts according to Example 1 and Comparative Examples 1 and 2. Figure 3 shows an SEM image of the catalyst according to Example 1. Figure 4 shows a TEM image of the catalyst according to Example 1. Figure 5 shows an enlarged TEM image of the catalyst according to Example 1. Figure 6 shows an HAADF-STEM image of the catalyst according to Example 1. Figure 7 shows the EXAFS analysis results of the catalysts according to Comparative Examples 1 and 2 and Example 1. Figure 8 shows the LSV measurement results of the catalysts according to Comparative Examples 1 and 2 and Example 1. FIG. 9 shows a graph of LSV results measuring the change in catalytic activity according to Examples 1 to 5. Specific details for implementing the invention
[0029] Terms such as first, second, and third are used to describe various parts, components, regions, layers, and / or sections, but are not limited thereto. These terms are used solely to distinguish one part, component, region, layer, or section from another part, component, region, layer, or section. Accordingly, the first part, component, region, layer, or section described below may be referred to as the second part, component, region, layer, or section without departing from the scope of the present invention.
[0030] The technical terms used herein are for the reference of specific embodiments only and are not intended to limit the invention. The singular forms used herein include plural forms unless phrases clearly indicate otherwise. As used in the specification, the meaning of "comprising" specifies certain characteristics, areas, integers, steps, actions, elements, and / or components, and does not exclude the presence or addition of other characteristics, areas, integers, steps, actions, elements, and / or components.
[0031] When it is stated that one part is "above" or "on" another part, it may be directly above or on the other part, or other parts may be involved in between. In contrast, when it is stated that one part is "directly above" another part, no other parts are interposed in between.
[0032] Unless otherwise defined, all terms used herein, including technical and scientific terms, have the same meaning as generally understood by those skilled in the art to which this invention pertains. Terms defined in commonly used dictionaries are further interpreted to have meanings consistent with relevant technical literature and the present disclosure, and are not interpreted in an ideal or highly formal sense unless otherwise defined.
[0033] Also, unless otherwise specified, % means volume %, and 1 ppm is 0.0001 volume %.
[0034] In this specification, the term “combination(s) of these” described in the Markush-type expression means one or more mixtures or combinations selected from the group consisting of the components described in the Markush-type expression, and means including any one or more selected from the group consisting of said components.
[0035] Hereinafter, embodiments of the present invention are described in detail so that those skilled in the art can easily implement the invention. However, the present invention may be embodied in various different forms and is not limited to the embodiments described herein.
[0037] Nanocarbon-based single-atom catalysts
[0038] A nanocarbon-based single-atom catalyst according to one embodiment of the present invention may comprise a carbon support; and a single-atom metal supported on the carbon support.
[0039] In the present invention, the “single-atom catalyst” means that the catalytic material is dispersed among one another in single-atom units and evenly supported on a carbon support, and is distinguished from nanoparticles or microparticles formed by the aggregation of the catalytic material being supported on the carbon support. By dispersing the catalytic material among one another in single-atom units on the carbon support, the catalyst has the advantage of having excellent activity and selectivity.
[0040] The carbon support may be conical in shape, specifically, may be conical in shape with an internal empty space. One end of the conical carbon support may be open, specifically, a relatively narrow end may be open. In the present invention, a relatively wide end positioned opposite to the narrow end may also be open, but is not particularly limited.
[0041] The cross-sectional diameter of the above-mentioned open end portion may be 0.1 nm to 5 nm, specifically 0.2 nm to 3 nm, and more specifically 0.3 nm to 2 nm.
[0042] In the present invention, the diameter of the cross-sectional end of the conical carbon support can be measured from the results of TEM analysis. Here, TEM analysis was performed using a Tecnai G2 F20, USA at an accelerating voltage of 200 kV at magnifications of 86,000 or 400,000. To prepare the TEM specimen, the carbon support powder was mixed with an ethanol solvent and then ultrasonically dispersed to prepare a mixed solution. Subsequently, the mixed solution was applied to a TEM grid and dried to prepare the specimen.
[0043] In a nanocarbon-based single-atom catalyst according to one embodiment of the present invention, the carbon support may comprise one or more selected from single-walled carbon nanotubes (SWCNT) or multi-walled carbon nanotubes (MWCNT).
[0044] A nanocarbon-based single-atom catalyst according to one embodiment of the present invention may include one or more carbon supports including the open end portion.
[0045] In addition, a nanocarbon-based single-atom catalyst according to one embodiment of the present invention may be a secondary particle formed by aggregating a plurality of primary nanocarbon-based single-atom catalyst particles, and the average particle size (D50) of the secondary particle may be 10 nm to 300 nm, specifically 20 nm to 200 nm, and more specifically 30 nm to 160 nm.
[0046] In the present invention, the average particle size of the secondary particles can be measured from SEM analysis images, wherein SEM analysis was performed at a magnification of 200,000 using a Nova Nano SEM 450, FEI, USA with an acceleration voltage of 10 kV. To prepare the SEM analysis sample, the carbon support powder was prepared by fixing it in powder form onto an analysis substrate.
[0047] A nanocarbon-based single-atom catalyst according to one embodiment of the present invention has a specific surface area of 50 m² 2 / g to 1000m 2 It can be in the range of / g, specifically 550m 2 / g to 900m 2 It may be in the range of / g, more specifically 590m 2 / g to 860m 2 / g can be in the range.
[0048] In XRD analysis of a nanocarbon-based single-atom catalyst according to one embodiment of the present invention, the FWHM of the peak at the position where 2θ is 26°±0.5 may be 1.44 arcsec or less.
[0049] The nanocarbon-based single-atom catalyst may include one or more single-atom metals selected from cobalt (Co), iron (Fe), nickel (Ni), rhodium (Rh), and iridium (Ir). Additionally, the nanocarbon-based single-atom catalyst may include one or more nonmetals selected from nitrogen (N), boron (B), sulfur (S), selenium (Se), phosphorus (P), fluorine (F), chlorine (Cl), bromine (Br), and iodine (I). For example, the nanocarbon-based single-atom catalyst may include one or more nonmetals selected from nitrogen (N), boron (B), sulfur (S), selenium (Se), phosphorus (P), fluorine (F), chlorine (Cl), bromine (Br), and iodine (I); one or more transition metals selected from cobalt (Co), iron (Fe), nickel (Ni), rhodium (Rh), and iridium (Ir); or a combination thereof. For example, the single-atom catalyst may include nitrogen (N), cobalt (Co), or a combination thereof. For example, the single-atom catalyst may include nitrogen (N) and cobalt (Co) simultaneously. For example, the single-atom catalyst may include nitrogen (N) or cobalt (Co).
[0050] More specifically, the above single-atom metal can be supported by nitrogen elements combined with carbon elements.
[0051] The single-atom metal included in the above nanocarbon-based single-atom catalyst may be included in an amount of 0.01 to 10 weight% based on the total weight of the nanocarbon-based single-atom catalyst, specifically 0.05 to 5 weight%, and more specifically 0.1 to 1.0 weight%. When the loading amount of the single-atom metal is within the above range, the catalyst can be evenly dispersed in a single-atom form on the carbon support, and the catalyst has excellent activity and selectivity.
[0052] Method for manufacturing nanocarbon-based single-atom catalysts
[0053] FIG. 1 is a schematic diagram of a method for manufacturing a nanocarbon-based single-atom catalyst according to another embodiment of the present invention.
[0054] Referring to FIG. 1, a method for manufacturing a nanocarbon-based single-atom catalyst according to another embodiment of the present invention may include the steps of: mixing a carbon precursor and a metal precursor and processing them in a dry gas phase process in an inert gas atmosphere to obtain a first intermediate; heat-treating the obtained first intermediate in an atmosphere that continuously supplies an oxygen-containing gas to obtain a second intermediate; and heat-treating the obtained second intermediate in an atmosphere that continuously supplies ammonia gas to obtain a nanocarbon-based single-atom catalyst.
[0055] The above method for manufacturing a nano-carbon-based single-atom catalyst comprises the step of obtaining a first intermediate by mixing a carbon precursor and a metal precursor and processing them in a dry gas phase process in an inert gas atmosphere, wherein the carbon precursor refers to a raw material of the carbon support and may include, for example, one or more selected from graphite, C2H2,CH4, C2H4, C2H6, and C2H5OH.
[0056] The above dry vapor phase process may be one or more processes selected from arc discharge, thermal chemical vapor deposition, plasma synthesis, high temperature plasma, plasma enhanced chemical vapor deposition, laser evaporation, laser ablation, and vapor phase growth.
[0057] The above dry vapor phase process may specifically be an arc discharge process. The arc discharge may be performed at a voltage of 10 to 50 V, specifically at a voltage of 20 to 40 V, and more specifically at a voltage of 25 to 35 V. Meanwhile, the arc discharge may be performed under a current of 50 to 300 A, specifically at a current of 100 to 200 A, and more specifically at a current of 150 to 200 A. By controlling the voltage and current of the arc discharge within the above ranges, there is an advantage in producing a catalyst in which a single-atom catalyst is uniformly dispersed and supported on a carbon support.
[0058] According to one embodiment of the present invention, the dry vapor phase process may be performed under a gaseous atmosphere of a non-metal-containing precursor. Specifically, an arc discharge may be performed under a gaseous atmosphere of a non-metal-containing precursor. For example, if a carbon precursor powder is arc discharged after filling a reaction chamber with a nitrogen-containing gas, nitrogen (N) can be evenly dispersed at a single-atom level on the resulting carbon precursor. Specifically, if a mixed powder of a carbon precursor and a metal precursor is arc discharged after filling a reaction chamber with a nitrogen-containing gas, nitrogen (N) and metal can be evenly dispersed at a single-atom level on the resulting carbon support.
[0059] The step of obtaining a second intermediate by heat-treating the first intermediate obtained above in an atmosphere where an oxygen-containing gas is continuously supplied may be a step of heat-treating while continuously supplying a gas containing oxygen. After loading the obtained intermediate into a chamber, heat treatment may be performed by gradually increasing the temperature while continuously supplying a gas containing oxygen. At this time, the supplied oxygen-containing gas may pass through the first intermediate located inside the chamber and then be discharged to the outside through the gas outlet of the chamber, and the inside of the chamber may be at atmospheric pressure. Specifically, the oxygen-containing gas may be air and may be supplied at a supply rate of 150 cc / min to 250 cc / min. The chamber temperature increase rate may be 3 ℃ / min to 6 ℃ / min. After raising the temperature of the chamber to a range of 200°C to 500°C, specifically to a range of 250°C to 450°C, more specifically to a range of 300°C to 400°C, the temperature can be maintained at the temperature for a predetermined time, specifically to 30 minutes to 180 minutes. By heat-treating the first intermediate under the above conditions, one end of the conical carbon support can be opened, specifically, a relatively narrow end can be opened.
[0060] The step of obtaining a nano-carbon-based single-atom catalyst by heat-treating the obtained second intermediate in an atmosphere where ammonia gas is continuously supplied may be a step of heat-treating while continuously supplying ammonia gas. After completing the step of preparing the first intermediate, the temperature is gradually increased while continuously supplying ammonia gas instead of oxygen-containing gas, to a temperature in the range of 550°C to 850°C, specifically to a temperature in the range of 600°C to 800°C. At this time, the heating rate may be 3°C / min to 6°C / min. Meanwhile, the ammonia gas supply rate may be in the range of 350 cc / min to 450 cc / min.
[0061] Meanwhile, nitrogen gas can be additionally mixed with the ammonia gas and supplied to the chamber. At this time, the nitrogen gas can be mixed in a ratio of 0 to 80 volume% of the ammonia gas.
[0062] By heat-treating the second intermediate under the above conditions, there is an advantage in that the specific surface area and strength of the nano-carbon-based single-atom catalyst produced can be further improved.
[0064] Preferred embodiments and comparative examples of the present invention are described below. However, the following examples are merely preferred embodiments of the present invention, and the present invention is not limited to the following examples.
[0065] <Comparative Example 1>
[0066] 20.6g of CoCl and 0.6g of Vulcan XC-72 were mixed in 150mL of acetone and then evaporated and dried in a rotary evaporator in a 45℃ water bath at 140rpm. Next, the metal mixture powder was mixed with the graphite powder and loaded into the chamber. A cathode was introduced into the reaction chamber for arc discharge, and after filling with a nitrogen atmosphere, an intense arc was generated by applying a voltage of 30V and a current of 150A for 5 minutes at a pressure of 300 torr. After the reaction was completed, the mixture was left under vacuum for 30 minutes and cooled to room temperature to obtain the catalyst.
[0067] <Comparative Example 2>
[0068] After loading the product obtained in Comparative Example 1 into the chamber, an air atmosphere was formed inside the chamber, and then air was supplied into the chamber at a supply rate of 200 cc / min while the temperature was raised to 300°C to 400°C at a heating rate of 5°C / min and maintained for 30 minutes. Then, the catalyst was obtained by cooling to room temperature.
[0070] <Example 1>
[0071] After loading the product prepared according to Comparative Example 2 into a chamber, an ammonia gas atmosphere was formed inside the chamber, and then nitrogen gas and ammonia gas were supplied into the chamber at a supply rate of 200 cc / min, while the temperature was raised to 700°C at a heating rate of 5°C / min and maintained for 1 hour. Then, the temperature was cooled to room temperature to obtain the catalyst.
[0073] <Examples 2, 3>
[0074] A catalyst was prepared in the same manner as in Example 1, except that the temperature was raised to 600℃ (Example 2) and 800℃ (Example 3) at a heating rate of 5℃ / min.
[0076] <Examples 4, 5>
[0077] A catalyst was prepared in the same manner as in Example 1, except that the temperature was raised to 700°C at a heating rate of 5°C / min and maintained for 60 minutes and 120 minutes.
[0079] (Evaluation Example 1: X-ray Diffraction XRD Analysis)
[0080] X-ray diffraction (XRD) analysis was performed on the catalysts prepared according to Comparative Examples 1 and 2 and Example 1, and the analysis results are shown in Fig. 2.
[0081] Referring to FIG. 2, it was confirmed that in the case of Example 1, the peak appearing near 25° exhibited a relatively sharp shape compared to Comparative Examples 1 and 2. In addition, the FWHM of the peak was calculated and shown in Table 1 below.
[0082] Referring to FIG. 2 and Table 1 below, it can be seen that the crystallinity of the catalyst according to Example 1 is relatively excellent.
[0083] The XRD analysis and FWHM calculation methods used conventional methods, and detailed descriptions are omitted in this specification.
[0084] Comparative Example 1 Comparative Example 2 Example 1 BET specific surface area (m 2 g -1 ) 84 366 696 XRD FWHM 2.08 1.92 1.44 D(002) distance (Å) 3.4 3.4 3.4 Lc size (nm) 4.1 4.44 5.92
[0085] (Evaluation Example 2: BET Analysis)
[0086] BET analysis was performed on the catalysts prepared according to Comparative Examples 1 and 2 and Example 1, and the analysis results are shown in Table 1.
[0087] Referring to Table 1, the BET area of the catalyst prepared according to Example 1 was found to be higher than that of Comparative Examples 1 and 2.
[0088] In the present invention, the “specific surface area” was measured using the Brunauer-Emmett-Teller Analysis method based on the nitrogen adsorption method, and a method was adopted to measure the specific surface area of the material by adsorbing and desorbing nitrogen gas onto the surface of a solid sample using the BET (Brunauer-Emmett-Teller) equation and measuring the amount of adsorption at different partial pressures.
[0090] (Evaluation Example 3: SEM and TEM Analysis)
[0091] Scanning electron microscope (SEM) analysis was performed on the catalyst prepared according to Example 1, and the observed 200,000x magnification SEM image is shown in Fig. 3.
[0092] Transmission electron microscopy (TEM) analysis was performed on the catalyst prepared according to Example 1, and the observed TEM image is shown in Fig. 4 and partially magnified in Fig. 5.
[0093] Fig. 4(a) is a TEM image at 86,000 magnification, and Fig. 4(b) is a TEM image at 400,000 magnification.
[0094] Referring to FIGS. 3 to 5, the catalyst prepared according to Example 1 has a roughly spherical particle shape, and it can be confirmed that the particles are secondary particles formed by aggregating a plurality of primary particles.
[0095] Meanwhile, referring to FIG. 5, it can be seen that the catalyst prepared according to Example 1 contains conical primary particles, and that the terminal portions of some conical primary particles have an open shape. Meanwhile, it can be seen that the diameter of the relatively narrow terminal portion of the conical primary particles is 5 nm or less, specifically 3 nm or less, and more specifically 2 nm or less.
[0096] As described above, it can be seen that the specific surface area of the catalyst prepared according to the present invention is increased by including cone-shaped particles with open ends.
[0098] (Evaluation Example 4: HAADF-STEM Analysis)
[0099] High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) analysis was performed on the catalyst prepared according to Example 1, and the analysis results are shown in Figure 6.
[0100] Referring to Fig. 6, it can be seen that single-atom Co metal is dispersed without aggregation within the catalyst prepared according to Example 1.
[0102] (Evaluation Example 5: EXAFS Analysis)
[0103] EXAFS analysis was performed on the catalysts prepared according to Comparative Examples 1 and 2 and Example 1, and the analysis results are shown in Fig. 7.
[0104] Referring to Fig. 7, it can be seen that the Co-N bond length (1.911 Å) of the catalyst prepared according to Example 1 is relatively shorter compared to Comparative Example 1 and Comparative Example 2, confirming that the bonding between Co and N is better formed.
[0106] (Evaluation Example 6: Evaluation of Catalytic Activity)
[0107] Linear sweep voltammetry (LSV) measurements were performed on the catalysts prepared according to Comparative Examples 1 and 2 and Example 1, and the results are shown in FIG. 8.
[0108] Referring to FIG. 8(a), it was shown that the reduction peak of the catalyst prepared according to Example 1 of the present invention increased compared to Comparative Example 1 and Comparative Example 2, and referring to FIG. 8(b), it can be confirmed that the catalyst according to Example 1 has higher performance than a commercial Pt catalyst when an oxygen reduction reaction is performed.
[0109] The LSV measurement results of the catalysts prepared according to Examples 1 to 3 are shown in FIG. 9(a), and the LSV measurement results of the catalysts prepared according to Examples 1, 3, and 4 are shown in FIG. 9(b).
[0110] Referring to FIG. 9(a), it can be seen that the catalysts prepared according to Examples 1 to 3 exhibit activity similar to that of commercial Pt catalysts.
[0111] Referring to Fig. 9(b), in the case of Example 5, where the heat treatment time was 180 minutes, the catalytic activity was found to be slightly reduced, which can be explained by the breakdown of the carbon structure.
[0113] Although preferred embodiments of the present invention have been described above, the present invention is not limited thereto and can be implemented with various modifications within the scope of the claims, the detailed description of the invention, and the attached drawings, and it is obvious that such modifications also fall within the scope of the present invention.
[0114] Therefore, the substantive scope of the present invention shall be defined by the appended claims and their equivalents.
Claims
Claim 1 A nanocarbon-based single-atom catalyst comprising: a carbon support; and a single-atom metal supported on the carbon support; wherein the carbon support is conical in shape with an internal empty space, and comprises one or more carbon supports having one end portion of the conical carbon support open. Claim 2 In claim 1, the specific surface area of the nanocarbon-based single-atom catalyst is 550 m² 2 / g to 900m 2 Nanocarbon-based single-atom catalyst in the / g range. Claim 3 A nanocarbon-based single-atom catalyst according to claim 1, wherein the FWHM of the peak located at 2θ 26°±0.5 in the XRD analysis of the nanocarbon-based single-atom catalyst is 1.44 or less. Claim 4 A nanocarbon-based single-atom catalyst according to claim 1, wherein the single-atom metal is included in a range of 0.1 wt% to 1.0 wt% based on the total weight of the nanocarbon-based single-atom catalyst. Claim 5 A nanocarbon-based single-atom catalyst according to claim 1, wherein the cross-sectional diameter of the open end portion is 2 nm or less. Claim 6 A nanocarbon-based single-atom catalyst according to claim 1, wherein the carbon support comprises one or more selected from single-walled carbon nanotubes or multi-walled carbon nanotubes. Claim 7 A nanocarbon-based single-atom catalyst according to claim 1, wherein the nanocarbon-based single-atom catalyst is a primary particle and the secondary particle is formed by aggregating a plurality of the primary particles. Claim 8 A nanocarbon-based single-atom catalyst according to claim 7, wherein the average particle size (D50) of the secondary particles is 30 nm to 160 nm. Claim 9 A nanocarbon-based single-atom catalyst according to claim 1, wherein the single-atom metal is supported by nitrogen elements bonded to carbon elements. Claim 10 A method for manufacturing a nanocarbon-based single-atom catalyst, comprising: a step of obtaining a first intermediate by mixing a carbon precursor and a metal precursor and processing them in a dry vapor phase process in an inert gas atmosphere; a step of obtaining a second intermediate by heat-treating the obtained first intermediate in an atmosphere that continuously supplies an oxygen-containing gas; and a step of obtaining a nanocarbon-based single-atom catalyst by heat-treating the obtained second intermediate in an atmosphere that continuously supplies ammonia gas. Claim 11 A method for manufacturing a nanocarbon-based single-atom catalyst according to claim 10, wherein, in the step of obtaining a nanocarbon-based single-atom catalyst by heat-treating the second intermediate obtained above in an atmosphere of continuously supplying ammonia gas, nitrogen gas is mixed with and supplied to the ammonia gas. Claim 12 A method for manufacturing a nanocarbon-based single-atom catalyst according to claim 10, wherein, in the step of obtaining a nanocarbon-based single-atom catalyst by heat-treating the obtained second intermediate in an atmosphere of continuously supplying ammonia gas, the heat treatment is performed at a temperature in the range of 550°C to 850°C. Claim 13 A method for manufacturing a nanocarbon-based single-atom catalyst according to claim 10, wherein, in the step of obtaining a nanocarbon-based single-atom catalyst by heat-treating the obtained second intermediate in an atmosphere of continuously supplying ammonia gas, the heat treatment is performed for 30 minutes to 180 minutes. Claim 14 A method for manufacturing a nanocarbon-based single-atom catalyst according to claim 10, wherein, in the step of obtaining a second intermediate by heat-treating the first intermediate obtained above in an atmosphere in which a gas containing oxygen is continuously supplied, the heat treatment is performed at a temperature in the range of 300°C to 400°C.
Citation Information
Patent Citations
Method for manufacturing single atom catalyst supported on carbon carrier
KR102182553B1